2015
DOI: 10.1089/jop.2015.0043
|View full text |Cite
|
Sign up to set email alerts
|

Atropine 0.01% Eyedrops Significantly Reduce the Progression of Childhood Myopia

Abstract: Atropine 0.01% significantly reduced the rate of myopic progression over 1 year with minimal side effects. It appears most effective in children with low initial myopia and may not control rapid myopic progression in some patients. Stronger concentrations of atropine may be required to slow rapid myopic progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
1
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 38 publications
6
80
1
6
Order By: Relevance
“…Recent studies have supported the use of 0.01% atropine to treat childhood myopia. 7,8 This comparatively lower dose of atropine appears to retain its effectiveness for inhibiting myopia, and results in a reduced severity of side effects such as allergies, loss of accommodation, and rebound. Some of those treated with 0.01% atropine still complain of muscarinic receptor (mAChR) blockade-induced complications, including photophobia and blurred vision; however, those symptoms are not severe enough to prompt a discontinuation of treatment.…”
mentioning
confidence: 99%
“…Recent studies have supported the use of 0.01% atropine to treat childhood myopia. 7,8 This comparatively lower dose of atropine appears to retain its effectiveness for inhibiting myopia, and results in a reduced severity of side effects such as allergies, loss of accommodation, and rebound. Some of those treated with 0.01% atropine still complain of muscarinic receptor (mAChR) blockade-induced complications, including photophobia and blurred vision; however, those symptoms are not severe enough to prompt a discontinuation of treatment.…”
mentioning
confidence: 99%
“…[2224] In the present study, the myopic progression, as measured by SE, and AL elongation, as measured by AL, were significantly reduced for participants in the intervention group than for those in the control group. These results indicate the promising efficacy of 0.5% ATE for myopia control in participants with LM.…”
Section: Discussionmentioning
confidence: 50%
“…A clinical trial used 0.01% ATE for the treatment of children with myopia, and found that it significantly decreased the rate of myopic progression over 1 year with minimal side effects. [22] However, such a low concentration (LC) of ATE may not control rapid myopic progression in some children. [22] Another study evaluated LC ATE (0.05–0.1%) for the treatment of school children with myopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Описана его высокая эффектив-ность в концентрации 0,01% в профилактике прогрес-сирования близорукости с минимизацией побочных эффектов [37,38].…”
Section: Introductionunclassified